Silicon Photonic Switch Subsystem With 900 Monolithically Integrated Calibration Photodiodes and 64-Fiber Package - Dumais, Patrick; Goodwill, Dominic J.; Celo, Dritan; Jiang, Jia; Zhang, Chunshu; Zhao, Fei; Tu, Xin; Zhang, Chunhui; Yan, Shengyong; He, Jifang; Li, Ming; Liu, Wanyuan; et al. (Journal of lightwave technology, 2018)
A packaged and fully operational 32 × 32 silicon photonic switch chip having 448 switch cells and 1856 crossings is demonstrated. The switch chip includes 900 monolithically integrated photodiodes used for calibrating the thermo-optic Mach-Zehnder switch cells. The calibration procedure employs an external laser source and follows a reachability-tree sequence to calibrate all switch cells. The accuracy of the calibration is demonstrated by the measurement of switch cell extinction ratios, for both states of each switch cell. The mean extinction ratio for both states is 35 dB. Arbitrary light path switching is demonstrated. Measurement of the channel-to-channel crosstalk was performed for a large number of aggressor and victim light path combinations. The matrix crosstalk is dominated by contributions from waveguide crossings. The die was wire-bonded to a custom ceramic package, to which a 68-fiber ribbon was permanently attached, which coupled the input and output optical signals to edge couplers on the chip through a waveguide pitch- and mode-concentrating silica chip. The fiber-to-fiber loss of on-chip loopback waveguides was less than 6.5 dB from 1530 to 1565 nm. The entirety of switch cells and monitors was driven by controller boards and A/D chips using a controller field-programmable gate array (FPGA). The calibration procedure was completed in less than 10 min using only the on-chip monitors, without off-chip detectors. The chip was recalibrated after six months storage, and the measured change in drive current was within the calibration uncertainty, indicating that the chip and driver are stable over time.